FACTORS AFFECTING FUNCTIONAL OUTCOMES AFTER SURGICAL FIXATION OF SCAPULAR FRACTURES (Vietnam Journal of Community Medicine, 2026)
ObjectiveTo evaluate functional outcomes and identify factors associated with postoperative results following surgical fixation of closed scapular fractures.MethodsA prospective study was conducted on 35 patients with closed scapular fractures who were treated with surgical fixation using locking plates at two tertiary trauma centers between December 2023 and December 2025. Clinical, radiological, and surgical variables were collected and analyzed. Functional outcomes were assessed using the Constant–Murley score and the EQ-5D index.ResultsAll patients achieved bone union within 6 months. The mean Constant score improved from 82.46 ± 6.06 at 3 months to 91.94 ± 4.70 at final follow-up. EQ-5D index increased to 0.9825 ± 0.072. Radiological parameters such as glenopolar angle, lateral border offset, and articular involvement were significantly associated with surgical indication and likely influenced outcomes.ConclusionSurgical fixation of scapular fractures using locking plates yields excellent functional outcomes. Preoperative fracture severity and restoration of anatomical alignment are key determinants of postoperative recovery.
Keywords: Scapular fracture; Functional outcome; Glenopolar angle; Lateral border offset; Shoulder function; Surgical treatment